Species-Specific Sensitivity and Levels of Beta-D-Glucan for the Diagnosis of Candidemia—A Systematic Review and Meta-Analysis - Nadir Ullah; Marco Muccio; Laura Magnasco; Chiara Sepulcri; Daniele Roberto Giacobbe; Antonio Vena; Matteo Bassetti; Malgorzata Mikulska (Journal of Fungi)
Background: 1, 3-ß-D-Glucan (BDG) is an antigen present in the cell wall of many pathogenic fungi and is used as a marker for the early diagnosis of candidemia and discontinuation of empirical treatment. Changes in the epidemiology of Candida species might have a negative impact on the performance of serum BDG. The aim of this study was to analyze the performance of BDG in candidemia diagnosis focusing on species-specific differences in BDG sensitivity and BDG levels. Methods: The PRISMA system was used for the systematic search. The following databases were searched for articles published from January 2010 to November 2023: PubMed, Science Direct, and Scopus. Results: A total of 21 studies that met the inclusion criteria were included, reporting data from 1633 patients with candidemia; 11 reported both sensitivity and specificity, 15 reported species-specific sensitivity, and nine reported species-specific BDG levels. The pooled sensitivity of BDG in all studies was 0.73 (95% confidence interval (CI), 0.66-0.80), while the pooled sensitivity and specificity in 11 studies were 0.81 (95% CI 0.73-0.89) and 0.80 (95% CI 0.74-0.87). BDG pooled sensitivity (all assays) and BDG levels (for assays with cutoff of 80 pg/mL) were the highest in C. krusei (currently Pichia kudriavzevii) and the lowest in C. auris: 0.76 and 417 pg/mL for C. krusei, 0.73 and 345 pg/mL for C. albicans, 0.74 and 356 pg/mL for C. glabrata (currently Nakaseomyces glabrata), 0.70 and 324 pg/mL for C. tropicalis, 0.63 and 95 pg/mL for C. parapsilosis, 0.51 and 62 pg/mL for C. auris, and 0.44 and 79 pg/mL for other Candida species. These differences were statistically significant for BDG sensitivity and levels of C. albicans, C. glabrata, C. krusei, and C. tropicalis compared to C. auris, C. parapsilosis, and other Candida species. Conclusion: The sensitivity of BDG in candidemia diagnosis depends on the Candida species, with the lowest being for C. auris and C. parapsilosis. This might have a clinical impact in centers where these species are prevalent.